Effect of persistence of left ventricular hypertrophy and left atrial dilatation after aortic valve replacement on early outcomes and survival: a prospective study - Murthy P., Hari Krishna; Chandra, Abha (International Surgery Journal, 2019)
Background: The objective of the study was to evaluate the early outcomes and survival in patients with severe aortic stenosis associated with concentric left ventricular hypertrophy following aortic valve replacement. Methods: This is a prospective study done at SVIMS, Tirupati, from June 2014 to September 2015 evaluating out comes and survival in patients undergoing primary isolated aortic valve replacement (AVR) for severe aortic stenosis, severe aortic stenosis with mild aortic regurgitation and severe aortic stenosis with moderate aortic regurgitation. Results: A total of 40 cases 26 males and 14 females aged 18 to 60 years (mean age, 48.5±13.4 years) underwent elective AVR. Left ventricular end diastolic diameter (p=0.008) at 6 months, a statistically highly significant difference in left ventricular mass preoperatively, at discharge, at 3rd and 6th month follow up. The difference in mean left ventricular mass index (LVMI) had declined from 244.425 to 141.100 at 6 months, showing a statistically highly significant difference in LVMI preop, at discharge, at 3rd month and at 6th month follow up. Conclusions: Patients with preoperative increase in LVMI, with large left atrial diameter carries a strong predictor of postoperative mortality for patients undergoing aortic valve surgery. We also conclude that there will be significant regression of LVMI following successful AVR. But, the decrease in LVMI is maximum during early three months and it is minimal though significant in the later course of follow up.